Novel Vector of Scrub Typhus in Sub-Antarctic Chile: Evidence From Human Exposure - Weitzel, Thomas; Silva, María; Martínez, Constanza; Stekolnikov, Alexandr; Pérez, Caricia; Pérez, Ruth; Vial, Cecilia; Abarca, Katia; Acosta, Gerardo (2021)
The exposure of a research team to chigger mites in southern Chile allowed the first identification of a trombiculid species as vector and reservoir of scrub typhus outside the tsutsugamushi triangle, providing unique insights into the ecology and transmission of this recently discovered rickettsial infection in South America. Versión publicada